RELATIONSHIP BETWEEN LEARNING MOTIVATION, LEARNING INDEPENDENCE AND STUDENT LEARNING ENVIRONMENT AT HOME WITH MATHEMATICS LEARNING RESULTS OF CLASS VIII STUDENTS OF SMP NEGERI 1 IMOGIRI - Khafid Baihaqi Iskak; Aris Thobirin (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
In this study low mathematics learning outcome was associated with many factors. Learning motivation learning self-reliance, and learning environment of students at home were some of the factors that might be linked to learning outcomes. This study aimed at identifying the presence or absence of a positive and significant relationship between student’s learning motivation, learning Self-Reliance,  learning environment at home with mathematics learning outcomes on grade VIII Junior High School I Imogiri in odd semester 2016/2017. The study population was all students in grade VIII of SMP Negeri 1 Imogiri, Bantul, Odd Semester in the academic year 2016/2017 consisting of seven classes with a total of 216 students. Samples were students of class VIII A as a class sample of 32 students using random sampling techniques to the class of techniques of data collection using questionnaires to determine learning motivation, learning self-reliance, and the learning environment of students at home, the test method was used to determine students' mathematics learning outcomes. the data analysis for hypothesis testing used simple linear regression analysis and multiple linear regression. The results showed that there was a positive and significant relationship between 1) learning motivation and the mathematics learning outcomes, with r = 0.4051991131;2) learning self-reliance and  mathematics learning outcomes, with r = 0.3976856431; 3) learning environment of students at home and mathematics learning outcomes, with r = 0.2964336693; 4) learning motivation and learning self-reliance with mathematics learning outcomes, with r = 0.4547066454; 5) learning motivation and learning environment of student at home with mathematics learning outcomes, with r = 0.4364494415; 6) learning self-reliance and the learning environment of students at home with mathematics learning outcomes, with r = 0.5279264426; 7) Student’s learning Motivation, learning Self-Reliance, and learning environment of Student at home with mathematics learning outcomes, with  = 3.639515644 > = 2.95, multiple correlation coefficient r = 0.29668461 with linear regression equation Y = -45.92818127 + 0.126289034 X1+0.68816534 X2+0,467791704 X3, SR = 8.943701276 %, SR = 57.00738487 % and SR  = 34.04891385 % and   SE  = 2.509143579 %, SE = 15.99334652 % and SE = 9.552377804 %.